Relationship between patterns of father-child activation, family functioning and child behavior - Bueno, Rovana Kinas (2022)
Relationships established in the family, such as the father-child activation relationship, interfere in the child's behavior. To understand the relationships between father-child activation, family functioning and child behavior, a study was conducted with 12 two-parent hetero-affective families with preschool children. It was used: Sociodemographic Questionnaire; Risk Situation; Family Adaptability and Cohesion Evaluation Scales; and Strengths and Difficulties Questionnaire. It was found that: eight children were classified as activated, three as under-activated and one as over-activated; the functioning of families is balanced and/or rigidly cohesive; and in the child's behavior it was verified high prosocial behavior and low scores in difficulties. Besides the activation relationship, family functioning was fundamental to understand the child's behavior.